Integrated model of economic impact of intersectoral One Health interventions for antimicrobial resistance (AMR) - CGIAR Research Program on Agriculture for Nutrition and Health (2020)
The model is completed and functional and ready to use. The next stage is to apply it to real-life examples in the field. Plans to do this in Vietnam are in preparation.